Simulation and analysis of an admission control mechanism for MPLS DS-TE - Mahmoud, Omer; Anwar, Farhat; Salami, Momoh Jimoh Emiyoka (Elsevier, 2008)
Providing quality of service (QoS) is one of the main challenges in the internet that has recently gained the interest of many researchers. The internet architecture was originally designed to provide IP based “best effort” services to all its applications. The best effort service could be acceptable for traditional applications such as email and web browsing, however, it is inadequate for new classes of emerging applications with real time data such as audio and video streaming. These new applications demand good quality of service from the network due to their inherent high data throughput (bandwidth) and low-latency requirements. Three main architectures were proposed by IETF in an effort to make the IP QoS a reality. They are integrated services (Intserv), differentiated services (DiffServ) and multiprotocol label switching (MPLS). Sometimes perceived as competitor, DiffServ and MPLS are in fact complementary developments that approach the QoS challenge from two different network perspectives. Thus these two approaches can be used together in order to combine their merits. This paper discusses an improved admission control which is aimed at enabling MPLS-TE tunnels differentiations (DS-TE tunnels). It presents a simulation based study which demonstrates the effectiveness of the proposed scheme where DiffServ EF traffic is mapped to MPLS tunnel to ensure stable performance for the traffic in the MPLS Domain.